ПОРЯДОК ПРОХОДЖЕННЯ ВІЙСЬКОВОЇ СЛУЖБИ ЯК ОБ’ЄКТ КРИМІНАЛІСТИЧНОГО ДОСЛІДЖЕННЯ - Бершов, Геннадій Євгенович (SUPREMANCE OF LAW, 2016)
The article emphasizes that military service is an integral element of activities to ensure the protection of the independence and territorial integrity of Ukraine, which takes place exclusively in the order and on the grounds established by law. It is emphasized that ensuring proper criminal legal protection of the order of military service, as well as timely detection of criminal violations in the specified sphere of social relations and their effective pre-trial investigation is impossible without understanding the essence and signs of military criminal offenses, as well as without characterizing the sphere that is criminally punishable - legal protection.